The Good, the Bad and the Ugly: Dialogical Ethics and Market Information - Kopf, Dennis A. (Journal of business ethics, 2010)
We apply dialogism to ethical thought to form a theory of Dialogical Ethics (DE). Specifically, DE is defined as the interplay between four historic ethical traditions: Formal (Kantian) Ethics, Content-Sense (Utilitarian) Ethics, Answerability Ethics, and Value/Virtue (Story) Ethics. On a broader level, DE can be understood as the interplay between the ethical ideas of society. We then use DE to analyze a number of problems in business including sweatshop labor and environmental degradation. To counteract these injustices, we propose two recommendations: (1) a rebalancing of Kantian and Utilitarian ethics in business with the ontological focus of Answerability and Value Ethics and (2) a revolution in business education. No longer can business education focus only on techne. Instead, educators must challenge students to develop phronesis, so that they become better able to understand how their actions and how our living stories interacts with the stories of others.